(untitled) (River Edge, N.J., 2003)
This book contains the papers presented at the ICM2002 Satellite Conference on Nonlinear Evolution Equations and Dynamical Systems. About 50 mathematicians and scientists attended the meeting — including E Witten (IAS), C Nappi (Princeton), K Khanin (Cambridge), D Phong (Columbia), d'Hoker (UCLA) and Peng Chiakuei (CAS). The book covers several fields, such as nonlinear evolution equations and integrable systems, infinite-dimensional algebra, conformal field theory and geometry.
Keywords: Evolution equations, Nonlinear,Differentiable dynamical systems,Bất phương trình vi phân,Phương trình vi phân thường; Congresses,Congresses,Tài liệu hội nghị, hội thảo,Tài liệu hội nghị, hội thảo